2015
DOI: 10.1167/iovs.14-14973
|View full text |Cite
|
Sign up to set email alerts
|

Cyclocoagulation of the Ciliary Bodies by High-Intensity Focused Ultrasound: A 12-Month Multicenter Study

Abstract: The new miniaturized HIFU EyeOP1 delivery device seems to be effective in decreasing IOP in patients with refractory glaucoma. The technology offers a good safety profile. (ClinicalTrials.gov number, NCT01338467.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
73
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 19 publications
18
73
1
5
Order By: Relevance
“…However, these success criteria have been previously used in several previous glaucoma surgical trials, particularly in the three main clinical studies evaluating the new ultrasonic ciliary body coagulation device, therefore facilitating comparisons of treatments outcomes among studies (Shaarawy et al 2009;Aptel et al 2011Aptel et al , 2014aDenis et al 2015). We found a mean IOP reduction of 30% in all patients treated, with an IOP decrease more than 20% in 63% of the patients (mean IOP reduction of 37% in those patients).…”
Section: Retreatmentmentioning
confidence: 72%
See 3 more Smart Citations
“…However, these success criteria have been previously used in several previous glaucoma surgical trials, particularly in the three main clinical studies evaluating the new ultrasonic ciliary body coagulation device, therefore facilitating comparisons of treatments outcomes among studies (Shaarawy et al 2009;Aptel et al 2011Aptel et al , 2014aDenis et al 2015). We found a mean IOP reduction of 30% in all patients treated, with an IOP decrease more than 20% in 63% of the patients (mean IOP reduction of 37% in those patients).…”
Section: Retreatmentmentioning
confidence: 72%
“…In the first multicenter study conducted in 52 patients with primary and secondary open-angle glaucoma, a first group of patients was treated with a 4-s exposure duration for each shot and a second group of patients with a 6-s exposure duration (Denis et al 2015). Patients were followed for at least 1 year.…”
Section: Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike reduced aqueous production, an increase in the aqueous outflow via the uveoscleral pathway is perhaps a less expected mechanism of action of UCP that nonetheless has been hypothesised on multiple occasions. 11,12,[21][22][23] Aptel observed in 2014 that a fluid space could be seen between the sclera and the ciliary body, and between the sclera and the choroid adjacent to treated areas, 21,24 and hypothesised that this corresponds to an area where the opening of the space should lead to an increase of the aqueous outflow via the uveoscleral pathway. A more recent prospective, observational monocentric study from Rouland and Aptel, using three-dimensional ultrasound biomicroscopy (UBM) that included 24 eyes from 19 patients, demonstrated that, in addition to reduction in aqueous humour production, UCP treatment caused an increase in aqueous humour outflow due to uveoscleral pathway opening.…”
Section: A: Control; B: Having Undergone Treatment With the Ultrasounmentioning
confidence: 99%